OPTIMIZATION OF IMMIGRATION DATA MANAGEMENT- TEMPLE APPLICATION AT THE BALIKPAPAN IMMIGRATION OFFICE - CATUR SUSANINGSIH; NADHIRA PUTERI ANDIKA (Jurnal Abdimas Imigrasi, 2022)
This paper raises the problems faced by the Immigration Office regarding the accumulation of archives and data recording that is not optimal in the rack locator application in the archive room of the Immigration Information and Communication Technology Section. Immigration data collected from various sections in the processing of immigration data faces obstacles in less than optimal collection, data input in the rack locator application, and data duplication, especially in applications for passports and residence permits. The author recommends a solution in the form of using a more efficient application for recording and compiling immigration documents, which can be used on various devices and minimizes data input errors. In addition, suggestions were given to provide barcode reading on the Drive Thru service, increase server capacity for the Secure Passport Storage Application (ASIAAP), and add mobile units in the Immigration Service Provide Foreigner Services Without Coming (SI BEKANTAN).